ลายพิมพ์ดีเอ็นเอของพืชวงศ์ลั่นทมบางชนิดด้วยเทคนิค Randomly Amplified Polymorphic DNA - เจนใจ สุธีพรวิโรจน์ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
Plants in family Apocynaceae, such as Plumeria sp., Adenium sp., Alstonia sp., Catharanthus sp. and Allamanda sp. are very famous as a household trees. The dominant feature of these plants were white latex which were in all parts of the trees but they have different features depending on their parts such as size, flower and leave. DNA relationship among some plants in family Apocynaceae was studied by RAPD technique. The efficiency of forty primers experimental found that the proper primer for making DNA fingerprint was nine primers which were O-01, O-18, OPB-07, OPB-08, OPD-20, OPW-09, R-37, R-55 and R-105. They produce 276 polymorphic DNA bands. The analysis of DNA fingerprint data was found that the relationship of DNA by using 3.2 phylic program and Tree Veiw 1.6.6. The result could be grouped by unweighted pair group method with arithmetic average (UPGMA) in five groups consisted of group 1 includes; Plumeria obtuse Linn., P. pudica Jacq., P. rubra L., Odontadenia macrantha (Roem. & Schult') Markgr., Kopsia fruticosa (Kerr) A. DC.), Carissa carandas L., Beaumontia grandiflora Wall., Cerbera odollam Gaertn., Dyera costulata (Miq.) Hook. f. Group 2 includes; Catharanthus roseus (L.) Don, Tabernaemontana pandacaqui Lam., Wrightia religiosa Benth., W. antidysenterica R. Br., Holarrhena pubescens Wall. ex G. Don, Alstonia scholaris (L.) R. Br. Group 3 includes; Nerium indicum Mill., Alyxia reinwardtii Blume., Strophanthus gratus Franch., Thevetia peruviana (Pers.) Schum. Group 4 includes; Allamanda blanchetii A. DC., A. cathartica L. and group 5 includes; Adenium obesum (Forssk.) Roem.& Schult. In terms of morphology, the comparison of figures found that the relationship of Apocynaceae DNA could not be harmonized clearly moreover, RAPD can be used as teaching aids in classroom as electronic book (E-book) for teaching science for Mattayom 6 students.